La Inteligencia Emocional en el desarrollo de las macro destrezas de estudios Sociales de los niños y niñas del cuarto grado de educación básica de la escuela fiscal “Amelia Guerrero” del cantón Chambo, Provincia de Chimborazo en el período académico 2014- 2015 - Reino Naranjo, Tatiana Marisol (2017)
The purpose of this research work is to determine strategies for understanding how Emotional Intelligence intervenes in the progress and development of the necessary capacities to face problems in life in family, social and school environments. The type of applied research is the exploratory-descriptive. The techniques used for data collection were: survey for teachers and observation for children. This allowed to evidence the problem. Some strategies were proposed in order to improve this context. It was necessary to consider that developing macro-skills in social studies subject is very important. The proposed techniques and strategies for 4 years old children contributed significantly to the learning process of the Social Studies subject according to the updated and strengthened curriculum of Basic General Education nowadays in force in Ecuador.